2013
DOI: 10.3389/fmicb.2013.00328
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of pathogenesis induced by bovine leukemia virus as a model for human T-cell leukemia virus

Abstract: Bovine leukemia virus (BLV) and human T-cell leukemia virus type 1 (HTLV-1) make up a unique retrovirus family. Both viruses induce chronic lymphoproliferative diseases with BLV affecting the B-cell lineage and HTLV-1 affecting the T-cell lineage. The pathologies of BLV- and HTLV-induced infections are notably similar, with an absence of chronic viraemia and a long latency period. These viruses encode at least two regulatory proteins, namely, Tax and Rex, in the pX region located between the env gene and the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
180
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 173 publications
(191 citation statements)
references
References 106 publications
1
180
0
10
Order By: Relevance
“…El VLB se ha convertido en una herramienta muy importante para el estudio del HTLV 1 ya que la infección que ambos producen es similar afectando las células T y las células B en el caso de VLB, no producen viremia crónica y su organización genética es igual (Aida et al, 2013).…”
Section: Introductionunclassified
“…El VLB se ha convertido en una herramienta muy importante para el estudio del HTLV 1 ya que la infección que ambos producen es similar afectando las células T y las células B en el caso de VLB, no producen viremia crónica y su organización genética es igual (Aida et al, 2013).…”
Section: Introductionunclassified
“…A large amount of data has been accumulated on the pronounced effect of expression of BLV proviral DNA, in particular tax gene, on stress reactivity in cells, apoptosis, cell renewal rates, and immune system of infected animals [7,43,44]. We have previously shown that it is in animals with high leukocytosis that expression of BLV RNA can be detected by RT-PCR [4].…”
Section: Erythrocyte and Leukocyte Profiles Of Peripheral Blood In Blmentioning
confidence: 99%
“…In 1871, bovine leukosis was first reported as yellowish nodules in the enlarged spleen of cattle (Leisering 1871;Aida et al 2013). Bovine leukosis is a neoplastic disease of cattle and is classified as two types: sporadic bovine leukosis (SBL; also known as T cell leukosis), and enzootic bovine leukosis (EBL) (also known as B cell leukosis).…”
Section: Introductionmentioning
confidence: 99%